Education action in health developed with recyclable material workers (Research, Society and Development, 2021)
Women waste pickers play a significant role in the recycling cycle of materials and, through their work, promote the sustainability of the planet in an attempt to reduce solid waste. Due to this situation they are exposed to occupational risks that directly influence their health and sexuality. The objective of the study is to report an educational health action developed with recyclable material workers on bodily transformations in the phases of women's lives. It is an experience report, with a qualitative, descriptive, applied approach, developed in a recycling cooperative in the Northwest region in the state of Rio Grande do Sul, with seven recyclable material workers, aged between 18 and 40 years. It was noticed that these women have little knowledge about their own body, reported doubts about the use of contraceptive methods and about the functioning of the female reproductive system, but demonstrate self-esteem and acceptance of their body image. The educational actions developed by nursing, with this class of workers, help to awaken a more comprehensive view of society and different social classes, in a professional performance that seeks humanized and egalitarian care.